Transactional analysis counselling in action - Stewart, Ian 1940- (Counselling in action, 1989)
Transactional analysis, with its simplicity of language and clarity of concept, offers an approach to counseling that promotes understanding and immediately catches the imagination. Yet, below this surface appeal is a profound theoretical structure. In this work, the author explains these theoretical principles by relating them to direct practice. He clearly illustrates the process of transactional analysis counselling from the first contact, through initial diagnosis and treatment planning, to contact-making and the planned treatment sequence. In addition, he offers useful suggestions for how best to deal with changing behavior patterns and emotions of clients.